Strategy to Development of Ecotourism in Kiluan Bay Lampung - Muhammad Reza; Lana Izzul Azkia; David Julian; Rizha Bery Putriani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Kiluan Bay is a coastal region in Tanggamus Regency, Lampung Province, with a very high potential for tourism. Increased levels of tourists may have a negative impact on Kiluan Bay's natural resources, one of which is the accumulation of trash. The ecosystem at Kiluan Bay may be impacted by trash accumulation, especially plastics. If these issues are not properly handled, it will have an impact on the sustainability of tourism activities and the preservation of the environment. Even so, this will have an effect on the local economy. In order to reduce the negative impacts of tourism activities that are not environmentally friendly, it is thought that the concept of ecotourism needs to be implemented at Kiluan Bay. The purpose of this study is to establish ecotourism development strategies that emphasize community knowledge at the local level. Survey techniques and interviews with relevant persons were used to collect the data. The results of the data collection were analyzed using a SWOT analysis to determine the alternative strategies required to support the implementation of the ecotourism concept in Kiluan Bay. The research showed that Kiluan Bay's ecotourism development is positioned in quadrant V (Growth/Stable). This viewpoint suggests that the ecotourism development strategy in Kiluan Bay, Lampung, must take the most of the existing opportunities. Developing an ecotourism management approach in Kiluan Bay that involves the community directly is one strategy that had to be implemented.